"Making It For Our Country": An Ethnography of Mud-Dyeing on Amami Ōshima Island. (2nd July 2020) - Linton, Charlotte
Abstract: Based on one year of fieldwork on Amami Ōshima island, southern Japan, this paper explores how traditional craft industries navigate the paradox between preservation and innovation. By focusing on dorozome (mud-dyeing), a process used in the production of the Amamian kimono cloth Oshima tsumugi, I look at how the skills embedded in this traditional but financially troubled industry evolve. I discuss the internal resistance to change that craftspeople experience locally, while concurrently facing external pressure from bureaucrats overseeing cultural preservation. I use the example of the dyeing company Kanai Kougei to show how they have responded to shifts in consumer culture, countering economic downturn through embracing innovation and diversity. This case study questions the very notion of tradition, by demonstrating that traditional craft practices in Japan have incorporated innovation throughout their development, often instigated by changing political, economic or technological circumstances. I argue that the current manifestation of dyeing practices in Amami are part of the ongoing evolution of local textile traditions. These have the potential to support economic and social sustainability at the site of production, and the wants of a global market looking for more environmentally sustainable commodities.